MODIFIKASI BERAS KETAN (Oryza sativa L. var. glutinosa) PADA PEMBUATAN GOLLA KAMBU (KUE TRADISIONAL MANDAR) - Sinar, Purnama; Rais, Muhammad; Sukainah, Andi (Jurnal Pendidikan Teknologi Pertanian, 2016)
Golla Kambu is a traditional cake of Mandar which made from glutinous rice, nira liquid and scrapes of coconut. The study have purpose to know which have short time of cooking to made Golla Kambu, and the level of hedonic by consumer of Golla Kambu. The study was conducted into two phases. The first phase, modificated the glutinous become instant rice and made Golla Kambu. Observed the time cooking of each treatment and conducted hedonic experiment. The data analysis with variance analysis (ANOVA), continued with Duncan (DMRT) on degree 5%. The result of study on the first phases showed that the bestÂ  instant glutinous rice from its boiling was on cooking in 10 minutes with rendemen 38.97% and cooking during 15 minutes with kamba density 0.24 g/ml and capacity of rehidrasi 3.87 ml/g. Meanwhile, the best instant rice on pan with exerting pressure was cook in 10 minutes with rendemen 38.48%, kamba density 0.24 g/ml and capacity of rehidracy 3.40 ml/g. The result of study on the second phase showed that Golla Kambu of instant rice with pressurized pan is the best kind of modification to shorten the cooking time of Golla Kambu and the best level of consumer acceptance is Golla Kambu of instant rice with pressurized pan